2008
DOI: 10.1159/000185538
|View full text |Cite
|
Sign up to set email alerts
|

Gender Dimorphism in High-Fat-Diet-Induced Insulin Resistance in Skeletal Muscle of Aged Rats

Abstract: Muscle resistance to insulin plays a key role in the metabolic dysregulation associated to obesity. A pro-inflammatory and pro-oxidant status has been proposed to be the link between dietary obesity and insulin resistance. Given the gender differences previously found in mitochondrial function and oxidative stress, the aim of the present study was to investigate whether this gender dimorphism leads to differences in the development of high-fat-diet-induced insulin resistance in rat skeletal muscle. Male and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
38
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 54 publications
3
38
0
1
Order By: Relevance
“…This difference was reflected in the greater divergence in body weight and liver adiposity between females fed the LF and HF diets. Similar gender dimorphic responses have been observed in rats fed HF diets (1,2) . These preliminary data provide evidence for sex-specific responses to high-fat intake but no apparent effect (up to 12 weeks of age) of the maternal low-folate insult.…”
supporting
confidence: 79%
“…This difference was reflected in the greater divergence in body weight and liver adiposity between females fed the LF and HF diets. Similar gender dimorphic responses have been observed in rats fed HF diets (1,2) . These preliminary data provide evidence for sex-specific responses to high-fat intake but no apparent effect (up to 12 weeks of age) of the maternal low-folate insult.…”
supporting
confidence: 79%
“…Previous studies in our laboratory performed in several tissues point to rat gender differences in morphology and mitochondrial function [7,[14][15][16][17][18][19]. Taking this background into account, the aim of the present study was to investigate the gender-related differences in rat liver mitochondrial morphology, function and biogenesis in response to the overweight induced by chronic feeding with a HFD, imitating the dietary habit increasingly found in developing countries.…”
Section: Introductionmentioning
confidence: 95%
“…HFD feeding increases the amount of substrate available for oxidation and the electron flux through the mitochondrial respiratory chain by enhancing free radical production. In addition, an impairment of antioxidant defenses has also been reported in diet-induced obesity [7]. An excess of ROS is harmful to cells but, within a certain level, ROS may be involved in the communication between mitochondria and the nucleus controlling the mitochondrial biogenesis process [8].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies demonstrated that sex dimorphism pointed towards a higher tendency of male rats to undergo metabolic syndrome manifestations when exposed to HFD feeding [19]. HFD feeding causes more detrimental effect in males due to higher insulin resistance, lower mitochondrial capacity, and lower facility to adapt to altered metabolic energy conditions [20].…”
Section: Introductionmentioning
confidence: 99%